Identification of optimal codons and analysis of phylogenetic relationship in Osteochilus salsburyi (Teleostei: Cypriniformes) based on complete mitogenome - Zhang, Cheng; Zhang, Shun; Tian, Zhe; Wang, Danli; Xu, Shanliang (Frontiers in Ecology and Evolution, 2023)
Mitogenomes are frequently used in the study of fish phylogenetic and evolutionary studies. However, there is currently no information available regarding the evolution history of Osteochilus salsburyi. To address this gap, an experiment was designed to gain a deeper understanding of this species by analyzing its mitochondrial structure, phylogenetic relationship, and optimal codon usage. The results showed that the complete mitogenome of O. salsburyi was 16,598 bp (GenBank Accession No: MW114837), including 22 tRNAs, 13 PCGs, two rRNAs, and two non-coding regions. The typical clover-leaf secondary structures of all 22 tRNA genes were detected. Moreover, the palindromic motifs TACAT and ATGTA of the D-loop tended to form hairpin loop structures, while the second-longest OL region contained a conserved motif 5’-GCCGG-3’. The relationships among Osteochilus species recovered from same mitochondrial characters were in agreement. The phylogeny based on nucleotide sequences supported the monophyly of the genus Osteochilus. Using the ΔRSCU (Relative Synonymous Codon Usage) method, six optimal codons (ACC, UAC, AAC, UGU, AGC, and GGC) were determined. Furthermore, we estimated the divergence time of O. salsburyi to be 154.06 Mya, during late Jurassic. Based on the maximum likelihood and Bayesian inference methods were used for phylogenetic analyses, and identical topologies were obtained. Our results supported that the classification of O. salsburyi as a species of the genus Osteochilus. In this study, the phylogenetic relationships among available Osteochilus mitogenomes were reported for the first time. This study should help us better understand the evolutionary status and species protection of O. salsburyi.